Richard Cook's jazz encyclopedia - Cook, Richard, 1957- (New York : Penguin Books, 2005)
Contains alphabetically arranged entries that provide information on significant events in the history of jazz, jazz artists and bands, and styles.
Library Journal.
Adult
Keywords: Jazz -- Encyclopedias; Jazz music -- Encyclopedias